P717 The use of combination biologic therapy in inflammatory bowel disease: A single tertiary-centre experience. (25th January 2019) - Panaccione, N; Novak, K; Seow, C; Devlin, S; Lu, C; Heatherington, J; Martin, M-L; Kaplan, G; Panaccione, R
Abstract: Background: Biologic therapy has revolutionised the care of inflammatory bowel disease (IBD). More recently, newer biologics have been approved. Despite multiple options, clinical remission rates at 1 year are approximately 40% for any single biologic agent. In addition, questions surround the efficacy of newer agents in controlling extra-intestinal manifestations (EIMs). This has raised interest in whether combination biologic therapy with agents of different mechanisms of action (MOA) can be used safely to increase overall efficacy and to control EIMs. The aim was to describe the clinical experience in IBD patients treated with combination biologic therapy at the University of Calgary IBD unit. Methods: A retrospective single-centre cohort study was performed at the University of Calgary of adult (≥18 years) IBD patients receiving combination biologic therapy All patients received 'add on' biologic therapy either to control medically refractory disease or to treat EIMs not controlled by a single agent. Safety and efficacy of the combination biologic therapy was assessed. Results: We identified 10 patients (9 Crohn's disease (CD), 1 ulcerative colitis (UC)) were treated with combination biologic therapy with mean follow-up of 64.8 weeks (range 10–118 weeks). All patients had failed > 3 previous biologics, All patients had a biologic added to existing biologic therapy. Primary indication to add a second biologic was medically refractory disease in 6 and control of EIMs in 4. Combinations of biologics used included: vedolizumab and adalimumab ( n = 3); vedolizumab and infliximab ( n = 3); vedolizumab and golimumab ( n = 2); vedolizumab and certolizumab ( n = 1); and ustekinumab and infliximab ( n = 1). Of the 6 who were on dual biologic therapy for medically refractory disease 3/6 (50%) demonstrated clinical improvement, and 3/6 (50%) demonstrated endoscopic response. Two patients (1 CD; 1 UC) underwent intestinal resection, but neither experienced a postoperative complication.The four whose primary indication was to control EIMS; anti-TNF therapy was added to vedolizumab and all patients had complete resolution of their EIMs. One patient developed community acquired pneumonia (CAP) on high-dose steroids, golimumab, and vedolizumab. All other combinations were well tolerated during the follow-up period. Conclusions: In this small, highly selective cohort of patients with IBD, a variety of combinations of biologic therapy were well tolerated. One patient developed CAP. The combination proved to be a successful strategy to control EIMs when anti-TNF therapy was added to vedolizumab. Further studies are needed to assess the comparative efficacy of combination strategies and long-term safety compared with single agents.